If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -13y = 7 Solving 5 + -13y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -13y = 7 + -5 Combine like terms: 5 + -5 = 0 0 + -13y = 7 + -5 -13y = 7 + -5 Combine like terms: 7 + -5 = 2 -13y = 2 Divide each side by '-13'. y = -0.1538461538 Simplifying y = -0.1538461538
| 7=-16t^2-75 | | 1.16-a-0.44444444=b-a | | (A-B)UD= | | -1/3y=-3 | | 6+5n=8n+9 | | 2x^7=1-x | | 15x-33+-57=90 | | 11740-x=x*0.6 | | 10-x=3.7 | | x-48+140=213 | | x-7+3x+1=90 | | 8*x+80=144 | | sqrt(6v+11)=sqrt(9v-2) | | 2x-2x+4=7 | | x+265-25=325 | | 7x-92+3x-8=90 | | 8x+37=77 | | 3x(x-4)-2x(x+5)= | | 7x-74+6x-83=90 | | 125000=7x-x | | 8x+86+3x+72=180 | | 4=2(2b+1) | | 15/x=30/7 | | -1*4=a | | -4+3=a | | (9+6i)(7+i)= | | -18+-7+-18+-7=a | | 1/2×-3/5=2/5 | | -10x-3(8+8x)=-6(x-4) | | 4=(2b+1)-60 | | 5x-3(1/2x-1)=-11 | | 3*-4+5=a |